Pojok Konseling: Layanan Gratis untuk Menjaga Kesehatan Mental Masyarakat Indonesia - K Kasmi; Salmiati S Ali; Suandara Pratiwi; N Nurwisah (Yayasan REDI Tiga Monas, 2024)
This service and research aims to identify and raise community awareness about the importance of mental health now and in the future. In addition, it aims to find out the extent of community knowledge about counseling. The program carried out in this service is a counseling corner that is attractively designed to give a curious effect to the public to visit the free counseling stand conducted at Alun-alun kidul Yogyakarta for 2 weeks by involving counselors, hypnotherapists and students of counseling guidance and psychology study programs in the city of Yogyakarta. This program is aimed at all groups of parents, children, teenagers, and various professions who are in that location. This program has good results in terms of community interest, from 2 weeks of the counseling corner program, it was found that new parents or young mothers have an interest in the correct parenting for children according to their developmental age and students who have personal problems. Another fact is that not all parents know the meaning and importance of counseling and mental health until the service team provides free education and counseling.